État de droit et droits indigènes dans le contexte d’une post-dictature : portrait de la criminalisation du mouvement mapuche dans un Chili démocratique - Fabien Le Bonniec (Amnis)
Despite being considered assimilated, dissolved into National States through their « pacification », the « fierce Mapuche indians » of Chile and Argentina have appeared on the national and international scene to claim their « historical rights ». The cultural but also political revival of the Mapuche movement in the post-dictatorship period can be seen in the antagonistic relations between the Chilean State, forestry companies and other economic interests, on the one side, and Mapuche communities and organizations on the other. The emergence of discourses and events that claim the Mapuche as social and political actors intensified the opposition with the State and state agents. The state violence which results from this confrontation is not a recent phenomenon, it's part of a secular relationship of domination/subordination between Chilean and indigenous societies, based on obsolete national ideologies that the Mapuche are questioning today in order to free themselves both physically and symbolically.